2010
DOI: 10.1007/s10389-009-0307-0
|View full text |Cite
|
Sign up to set email alerts
|

Use and understanding of nutrition information on food labels in six European countries

Abstract: AimThe goal of the study was to investigate the use of nutrition information on food labels and understanding of guideline daily amount (GDA) front-of-pack nutrition labels in six European countries.Subjects and methodsIn-store observations and in-store interviews were conducted in major retailers in the UK (n = 2019), Sweden (n = 1858), France (n = 2337), Germany (n = 1963), Poland (n = 1800) and Hungary (n = 1804), supplemented by questionnaires filled out at home and returned (overall response rate 50.3%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
273
5
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(315 citation statements)
references
References 11 publications
27
273
5
10
Order By: Relevance
“…Furthermore, even if there was no overreporting in our study, we cannot know whether people who use labels more often use these labels as a decision aid to buy the healthiest product. In other words, we do not know whether label use translates into a healthier diet (see the last part of Grunert et al's conceptual framework of food label use (13,14) ). As our results suggest that people who are generally interested in health and healthy eating use labels more often than others, we can speculate that they may use labels for choosing healthy foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, even if there was no overreporting in our study, we cannot know whether people who use labels more often use these labels as a decision aid to buy the healthiest product. In other words, we do not know whether label use translates into a healthier diet (see the last part of Grunert et al's conceptual framework of food label use (13,14) ). As our results suggest that people who are generally interested in health and healthy eating use labels more often than others, we can speculate that they may use labels for choosing healthy foods.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also supported the importance of health-related aspects for label use (see references (1), (2) and (5) for reviews of this literature). For example, having a strong belief in a relationship between diet and cancer, interest in healthy eating and being confident that one is able to eat healthily were associated with whether participants used labels at all (11)(12)(13)(14) . Furthermore, Petrovici and Ritson (15) found that self-reported nutrition knowledge and health motivation were positively related to frequency of label use.…”
mentioning
confidence: 99%
“…Standard attributes used in market research on product labelling were used in the survey. The surveys were conducted in English and French and took place August [16][17][18][19][20][21]2011. The results were weighted by age, region and gender according to Statistics Canada 2006 Census data.…”
Section: Methodsmentioning
confidence: 99%
“…) varies considerably across population subgroups. Acceptability, understanding and ensuing use are lower among men, the elderly, persons having low socio-economic status and individuals with little nutritional knowledge (3,7,(12)(13)(14) . Other features, including price, brand name, claims and ingredient lists, compete with nutrition labels for the attention of the consumer during purchasing; perception of nutrition labels thus differs according to consumer attention to such features (3,12,(14)(15)(16) .…”
mentioning
confidence: 99%
“…Previous studies compared acceptability and understanding of FOP label formats according to sociodemographic and economic factors, nutrition knowledge and interest in other characteristics of packaged foods (4)(5)(6)(7)12,14,17) . However, they did not take into account dimensions constituting acceptability so as to more accurately define profiles of label perception and elucidate their relationship with individual characteristics.…”
mentioning
confidence: 99%